Organizational Development: Analysis of Return on Investment, Training Needs Analysis, Job Enrichment and Competency (Literature Review) - Safariningsih, Ratna Tri Hari; Fachrial, Peppy; Widodo, Rintis Eko; Febrian, Wenny Desty; Marlita, Devi (Dinasti Publisher, 2024)
The purpose of this literature research is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article Organizational Development: Analysis of Return on Investment, Training Need Analysis, Job Enrichment, and Competence is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is using literature studies or reviewing relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Return on investment has an effect on Organizational Development; 2) Training Need Analysis has an effect on Organizational Development; 3) Job Enrichment has an effect on Organizational Development; and 4) Competence has an effect on Organizational Development.